Lande: The Calais 'Jungle' and Beyond - Mallet, Sarah (Bristol University Press, 2019)
Available Open Access under CC-BY-NC licence. How can Archaeology help us understand our contemporary world? This ground-breaking book reflects on material, visual and digital culture from the Calais "Jungle" - the informal camp where, before its destruction in October 2016, more than 10,000 displaced people lived. LANDE: The Calais 'Jungle' and Beyond reassesses how we understand 'crisis', activism, and the infrastructure of national borders in Refugee and Forced Migration Studies, foregrounding the politics of environments, time, and the ongoing legacies of empire. Introducing a major collaborative exhibit at Oxford's Pitt Rivers Museum, the book argues that an anthropological focus on duration, impermanence and traces of the most recent past can recentre the ongoing human experiences of displacement in Europe today.Available Open Access under CC-BY-NC licence. How can Archaeology help us understand our contemporary world? This ground-breaking book reflects on material, visual and digital culture from the Calais "Jungle" - the informal camp where, before its destruction in October 2016, more than 10,000 displaced people lived. LANDE: The Calais 'Jungle' and Beyond reassesses how we understand 'crisis', activism, and the infrastructure of national borders in Refugee and Forced Migration Studies, foregrounding the politics of environments, time, and the ongoing legacies of empire. Introducing a major collaborative exhibit at Oxford's Pitt Rivers Museum, the book argues that an anthropological focus on duration, impermanence and traces of the most recent past can recentre the ongoing human experiences of displacement in Europe today.